Examining Factors Correlating with Social Commerce Behavior in Generation X - Harnadi, Bernardinus; Astari, Aurelia Inten; Suciarto, Sentot (SISFORMA, 2024)
The purpose of this study was to investigate the behavioral factors that influence the acceptance of Generation X in making purchases at social commerce.The research was conducted using the FGD method and interviews with representatives of generation X and social media experts to capture the phenomenon of this generation's acceptance of social commerce technology. A literature review study was carried out to reveal the factors that influence the acceptance of social commerce and propose hypotheses and research models based on these findings. The questionnaire was developed based on the hypothesis and distributed to this generation as many as 189 respondents using a purposive sampling method. Data testing was carried out using descriptive statistical methods, validity, reliability, and correlation tests. Analysis of individual respondent factors was carried out to reveal the characteristics of generation X. Correlation analysis was carried out to gain insight into the relationship between the factors studied and the acceptance factor of generation X for social commerce technology.The results of this study will provide insight into the buying behavior of Generation X in making purchases on social commerce. These insights will be useful to marketing scientists, those wishing to do business with this generation and marketing policy makers. How to use the factors resulting from this research to attract generation X to purchase products in social commerce..